Avoidance Prone Individuals Self Reporting Behavioral Inhibition Exhibit Facilitated Acquisition and Altered Extinction of Conditioned Eyeblinks With Partial Reinforcement Schedules - Allen, Michael T.; Myers, Catherine E.; Servatius, Richard J. (Frontiers in Behavioral Neuroscience, 2014)
Avoidance in the face of novel situations or uncertainty is a prime feature of behavioral inhibition which has been put forth as a risk factor for the development of anxiety disorders. Recent work has found that behaviorally inhibited individuals acquire conditioned eyeblinks faster than non-inhibited individuals in omission and yoked paradigms in which the predictive relationship between the conditioned stimulus (CS) and unconditional stimulus (US) is less than optimal as compared to standard training with CS-US paired trials (Holloway et al., 2014). In the current study, we tested explicitly partial schedules in which half the trials were CS alone or US alone trials in addition to the standard CS-US paired trials. One hundred and forty nine college-aged undergraduates participated in the study. All participants completed the Adult Measure of Behavioral Inhibition (i.e., AMBI) which was used to group participants as behaviorally inhibited and non-inhibited. Eyeblink conditioning consisted of 3 US alone trials, 60 acquisition trials, and 20 CS-alone extinction trials presented in one session. Conditioning stimuli were a 500 ms tone conditioned stimulus (CS) and a 50-ms air puff unconditional stimulus (US). Behaviorally inhibited individuals receiving 50% partial reinforcement with CS alone or US alone trials produced facilitated acquisition as compared to non-inhibited individuals. A partial reinforcement extinction effect was evident with CS alone trials in behaviorally inhibited but not non-inhibited individuals. These current findings indicate that avoidance prone individuals self-reporting behavioral inhibition over-learn an association and are slow to extinguish conditioned responses when there is some level of uncertainty between paired trials and CS or US alone presentations.